College skills : intermediate English - Pattison, Tania; Coast Mountain College; BC Open Textbook Project; BCcampus (Coast Mountain College, 2018)
"This book has been written for adult students of English Language Arts at a Grade 10 level. As such, it meets the criteria established by the British Columbia Ministry of Education while providing content suitable for adult learners. The goal of the book is to help students develop skills in reading, writing, language use, and study skills. The book is divided into ten units, each of which focuses on a specific theme; these include food, work, art, money, nature, and more. All units follow the same sequence. Within each unit, students encounter two reading passages; these are followed by questions designed to improve comprehension skills, vocabulary, and critical thinking skills. Reading skills sections focus on tasks such as identifying bias, determining author purpose, and making personal connections with the text. Writing skills sections enable students to develop their skills at the paragraph level though such tasks as comparing/contrasting, discussing causes and effects, and writing persuasive pieces; creative writing, blogging, and letter writing are also included. There is work on language use, such as sentence structure, summarizing, paraphrasing, and so on. Study skills are also presented, with guidelines on time management, self-awareness, managing stress, and avoiding academic dishonesty. Where possible, the content is specific to British Columbia, including First Nations peoples. Throughout the book, students are encouraged to think critically about the issues presented to them, whether these are related to dietary habits, worker safety, the value of art, or a variety of other topics. Each unit contains several 'Think about It!' activities, where students are encouraged to share their own opinions, either orally or in writing. The goal is that students finish the book with a greater understanding of reading and writing skills; at the same time, they will develop a greater insight into their own opinions on a variety of topics relevant to their lives."--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on August 22, 2018).
Keywords: English language -- Textbooks; Electronic books